Effectuation processes of social media and student entrepreneurs in South Korea - Choi, Hwanho (Journal of Small Business Management, 2023)
This paper investigates the effectuation processes of student entrepreneurs in their utilization of social media. In-depth interviews conducted with student entrepreneurs in South Korea revealed that they have experienced a gap between the uses of means available for entrepreneurship and the realization of their effects. To narrow that gap, the student entrepreneurs have drawn from a concept of effectual endeavor that implies the engagement of an effectual process until the materialization of some level of effects is reached. To overcome the uncertainty that student entrepreneurs face while utilizing social media, the findings suggest that they have commonly adopted a perceived perseverance affordability to routinize and attain consistency for social-media uses and a flexible approach to leverage contingencies and create endogenous opportunities while utilizing social media.
Keywords: Effectuation; social media; student entrepreneur; uncertainty